2018
DOI: 10.11646/zootaxa.4370.5.1
|View full text |Cite
|
Sign up to set email alerts
|

Excavating sponges from the Pacific of Central America, descriptions and a faunistic record

Abstract: Excavating sponges are one of the main groups of bioeroders in coral reefs. Their diversity has been thoroughly studied in some regions: in the Caribbean, the Mediterranean, and the Indo-Pacific, including the Mexican Pacific. However, there is a lack of information from the Pacific of Central America, with only a few records from Panama and Costa Rica. This study provides additional distributional records and taxonomic descriptions of species collected between 2011 and 2016 at nine localities along the Pacifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 540 publications
(9 citation statements)
references
References 0 publications
0
5
0
4
Order By: Relevance
“…La identificación de la esponja fue realizada con el apoyo de la literatura especializada (fig. 2a, b; Carballo et al, 2004;Laubenfels, 1932;Pacheco et al, 2018). La longitud del largo de las almejas fue medida con un vernier (± 0.1 cm) y fue determinada como la distancia entre el extremo anterior y posterior de las valvas de cada almeja (Osuna-García, 2004).…”
Section: Materiales Y Métodosunclassified
“…La identificación de la esponja fue realizada con el apoyo de la literatura especializada (fig. 2a, b; Carballo et al, 2004;Laubenfels, 1932;Pacheco et al, 2018). La longitud del largo de las almejas fue medida con un vernier (± 0.1 cm) y fue determinada como la distancia entre el extremo anterior y posterior de las valvas de cada almeja (Osuna-García, 2004).…”
Section: Materiales Y Métodosunclassified
“…Our preliminary results are inconclusive with regard to the identification of this Ecuadorian Cliona material, as no DNA sequence has been published for C. eu-ryphylle, let alone for an Atlantic record of the species. It is also possible that the Ecuadorian species might belong to a distinct species, rather than suppose its crossing of the isthmus through the Panama Canal, as explicitly suggested by Pacheco et al (2018). Previous records of C. euryphylle need to be revised in an integrative approach with more extensive sampling and molecular analyses with higher resolution capabilities.…”
Section: Systematicsmentioning
confidence: 99%
“…However, a series of records exists that have been considered indicative of the species' transisthmian distribution (Carballo et al 2004;Vega 2012;Pacheco et al 2018). These report on sponges bearing tylostyles up to 368 µm long, and 11 µm thick (Carballo et al 2004;Vega 2012) respectively, but also, in the case of Pacific Costa Rican specimens, only up to 300 × 8 µm (Pacheco et al 2018), which considerably approach values originally reported by Topsent. On the other hand, spirasters appear to fall short from those of Topsent, up to nearly 50% longer.…”
Section: Systematicsmentioning
confidence: 99%
See 2 more Smart Citations